On the Historical development of the Liturgy - Baumstark, Anton, 1872-1948 (Book collections on Project MUSE., 2011)
Trained in classical and oriental philology, Anton Baumstark (1872-1948) was prodigious as a scholar studying the literature, art, and liturgy of the whole church--Oriental, Eastern, and Western. Comparative liturgy, his method for studying the historical development of the liturgy as an organism, has had a lasting influence, notably on the liturgical study of the Christian East. --Book Jacket.